Terrorism in the 2015 Election Period in Turkey: Content Analysis of Political Leaders' Social Media Activity - Guneyli, Ahmet; Ersoy, Metin; Kiralp, Sevki (Graz Univ Technolgoy, Inst Information Systems Computer Media-Iicm, 2017)
In this research, a case study was conducted, analyzing the Twitter messages posted between July and November 2015 by six political leaders in Turkey. The Twitter messages posted by President Erdogan, AKP's leader Davutoglu, CHP's leader Kilicdaroglu, MHP's leader Bahceli and HDP's co-chairs Demirtas and Yuksekdag were all examined. The analysis focused primarily on the messages that were related to terrorism. The research utilized a descriptive and qualitative approach as well as thematic content analysis. To consolidate the thematic content analysis, numerical data (total word amount and arithmetic mean), charts and tables were used. During the relevant period, terrorism and political instability dominated Turkish politics, and, on 1 November 2015, early elections were held. This research concluded that the six leaders differed in their approaches towards terrorism, which constituted a key issue for the political leaders in Turkey by dominating the political discourse during the electoral campaign.
Keywords: Political discourse; Turkey; Elections; Twitter; Terror; Content Analysis